2003
DOI: 10.1037/h0086947
|View full text |Cite
|
Sign up to set email alerts
|

Boundaryless psychology: A discussion.

Abstract: This article is divided into three parts. In the introduction, I echo the case for breaking down boundaries. In the Article Critiques, I point out some of the good points and some concerns about each of the empirical articles in this section. In the General Comments, I design a two-dimensional matrix to help researchers decide how to best break down barriers in their research. This matrix has Order of Distance Between Fields on one axis and Theory Development on the other. In order of proximal to distal, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…It is important for psychologists across Canada to work together and talk to each other, proud of their traditions in both science and practise. Duffy (2003) outlined some of the benefits of organising psychology around a common theme. Sternberg (2004) suggested that this common theme could be culture as all psychological phenomena should be interpreted within the cultural context in which they occur.…”
Section: The Importance Of a United Disciplinementioning
confidence: 99%
“…It is important for psychologists across Canada to work together and talk to each other, proud of their traditions in both science and practise. Duffy (2003) outlined some of the benefits of organising psychology around a common theme. Sternberg (2004) suggested that this common theme could be culture as all psychological phenomena should be interpreted within the cultural context in which they occur.…”
Section: The Importance Of a United Disciplinementioning
confidence: 99%
“…Il est important que les psychologues de partout au Canada travaillent ensemble et communiquent les uns avec les autres, qu'ils soient fiers de leurs contributions à la science et à la pratique. Duffy (2003) a souligné certains avantages à organiser la psychologie autour d'un thème commun. Selon Sternberg (2004), ce thème commun pourrait être la culture, puisque tous les phénomènes psychologiques gagnent à être interprétés en fonction du contexte culturel dans lequel ils se produisent.…”
Section: L'importance D'une Discipline Unieunclassified
“…All these areas ought to be represented among the psychology papers published in the journal. Duffy (2003) outlined some of the benefits of organizing psychology around a common interest. In our case, the common interest is aging.…”
Section: University Of Reginamentioning
confidence: 99%